From Influenza Virus to Novel Corona Virus (SARS-CoV-2)–The Contribution of Obesity - Bhattacharya, Indranil; Ghayor, Chafik; Pérez Dominguez, Ana; Weber, Franz E. (Frontiers in Endocrinology, 2020)
From the beginning of 2020, the governments and the health systems around the world are tackling infections and fatalities caused by the novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) resulting in the coronavirus disease 2019 (COVID-19). This virus pandemic has turned more complicated as individuals with co-morbidities like diabetes, cardiovascular conditions and obesity are at a high risk of acquiring infection and suffering from a more severe course of disease. Prolonged viral infection and obesity are independently known to lower the immune response and a combination can thus result in a “cytokine storm” and a substantial weakening of the immune system. With the rise in obesity cases globally, the chances that obese individuals will acquire infection and need hospitalization are heightened. In this review, we discuss why obesity, a low-grade chronic inflammation, contributes toward the increased severity in COVID-19 patients. We suggest that increased inflammation, activation of renin-angiotensin-aldosterone system, elevated adipokines and higher ectopic fat may be the factors contributing to the disease severity, in particular deteriorating the cardiovascular and lung function, in obese individuals. We look at the many lessons learnt from the 2009 H1N1 influenza A pandemic and relate it to the very little but fast incoming information that is available from the SARS-CoV-2 infected individuals with overweight and obesity.